Successful Prolonged Mechanical CPR in a Severely Poisoned Hypothermic Patient: A Case Report. (23rd August 2012) - Piacentini, Alberto; Volonte', Maurizio; Rigamonti, Marcello; Guastella, Elisa; Landriscina, Mario
Abstract : Mechanical cardiopulmonary resuscitation (m-CPR) devices are an alternative to manual CPR, but their efficacy has been subject to debate. We present a case of a patient with full-neurologic recovery after prolonged m-CPR. The patient presented with severe hypothermia (internal temperature 24°C) and poisoning (sedatives/hypnotics). Hepatic perfusion and metabolism are considered keys to restore spontaneous circulation. During this period no problems related to the device or patient positioning were encountered. Delivery of high-quality CPR and prolonged resuscitation were achieved. We confirm that ventilations asynchronous with chest compressions can be a problem. Reduction in chest measurements can hamper lung ventilation. A synchronous mode of manual ventilation (30 : 2) seems to be the best solution. The patient had an initial period of manual CPR. No damage to any organ or structure was noted. This case is of further interest because our EMS helicopters can fly 24 hours a day and m-CPR devices could play an important role as a "bridge" in patients when active rewarming by cardiopulmonary bypass is indicated (CPB).